Elastic-viscoplastic behavior of filament winding CFRP: experimental investigation and multiscale analysis - Tetsuya MATSUDA; Akito TAMURA; Tomoya TAKAHASHI; Naoki MORITA; Masahito UEDA; Wataru IWASE; Tomohiro YOKOZEKI (Mechanical Engineering Journal)
In this study, tensile properties including material nonlinearity (viscoplasticity) of carbon fiber-reinforced plastics manufactured by the filament winding method (FW-CFRPs) are experimentally investigated, and numerically analyzed using a three-scale homogenization method. First, tensile tests of FW-CFRPs made of towpregs with carbon fibers and an epoxy resin are conducted using coupon specimens with five kinds of laminate configurations, i.e., [0]4, [90]8, [0/90]2s, [45/-45]2s and [63/-63]2s. Based on the stress-strain relationships obtained, tensile properties of the FW-CFRPs and their dependence on the laminate configurations are examined. To analyze such properties, multiscale elastic-viscoplastic analysis of the FW-CFRPs is performed using the three-scale homogenization method developed by the authors. For this, meso-scale unit cells consisting of fiber tows without or with crimps and a micro-scale semiunit cell consisting of the carbon fiber and epoxy are prepared. In addition, material constants of the epoxy are determined by tensile tests of epoxy specimens. Using the unit cells and material constants, multiscale tensile analysis of the FW-CFRPs is conducted. It is shown that the analysis results are in quantitatively good agreement with the experimental results, validating the present analysis method. It is also shown that the existence of crimps in fiber tows causes nonlinear behavior of the [0/90] FW-CFRP, resulting in lower macroscopic stress compared with the case without crimps.